Decentralized Power Management for Electrical Power Systems in More Electric Aircrafts - Myungchin Kim (Electronics, 2018)
In order to implement reliable and flexible power management among energy sources, a decentralized power management approach for electrical power systems (EPSs) in the more electric aircraft (MEA) is studied. Considering the increased use of electrical power for various functions, the performance of MEA would be determined by the design and operation of the EPS. By using a virtual impedance that includes both a resistive term and an inductive term, autonomous power sharing is realized. Because of the frequency dependence in the virtual impedance, different power sharing ratios between steady state and transient state can be considered. Not only the operation of various power sources is coordinated without supervision of a centralized controller, but also the operation profile of each source can be adjusted to meet output characteristics of each source. To demonstrate the effectiveness of the proposed approach, a series of simulations that consider various virtual impedance configurations were conducted. The proposed approach contributes to a higher level of operational flexibility, while enabling reliable and cost-effective management of MEAs.